Effects of initial disturbances and grazing regime on native grassland invasion by Eragrostis plana in southern Brazil - Baggio, Rodrigo; Medeiros, Renato Borges de; Focht, Telmo; Boavista, Lidiane da Rosa; Pillar, Valério D.; Müller, Sandra C. (Perspectives in ecology and conservation, 2018)
[Display omitted] •Eragrostis plana invasion in native grasslands in southern Brazil is a serious conservation problem due to its low palatability and ability to rapidly spread.•Soil scarification increased the rate of E. plana invasion and changed the composition and diversity of plant communities.•Levels of E. plana invasion were low in all grazing systems when soils were undisturbed. Moderately grazed grasslands can resist the invasion by E. plana. Extensive invasion of the Campos grasslands of southern Brazil by the South African grass, Eragrostis plana, is a serious conservation problem due to its low palatability and ability to quickly spread. Here, we experimentally evaluated the effects of grazing management and initial disturbance on invasibility of native grassland community by E. plana. The experiment, a split-plot complete block design with three replications, was established in 2004 in non-invaded native grassland. Grazing management treatments were assessed in main plots (continuous grazing, rotational grazing, and grazing exclusion). The initial disturbance treatments (light grazing, heavy grazing, and heavy grazing plus soil scarification) were applied in subplots before the sowing of standard amounts of E. plana seeds. The initial disturbances heavy grazing and heavy grazing plus soil scarification simulated the introduction of exotic forage species. We monitor plant species composition and diversity along six years after the experiment starting. The effects of grazing management and initial disturbance on community invasibility were significant and showed interaction. Heavy grazing plus soil scarification increased the rate of E. plana invasion and produced more pronounced changes in species composition than the other treatments. Plots under grazing exclusion, rotational or continuous grazing without soil scarification had low levels of invasion (<10% cover). But exclusion also changed community composition and decreased diversity, while rotational and continuous grazing maintained community structure. The invasion can be largely prevented on undisturbed grassland by employing either rotational or continuous grazing management. If the livestock producers want to introduce another forage species in their natural grasslands and, at the same time, do not run the risk of opening space for E. plana should avoid the use of soil scarification.